(untitled) (NAU Journal of Technology and Vocational Education, 2025)
This study investigated the relationship between self-efficacy and student’s academic performance in technical drawing in Edo State technical colleges. A correlational research design was adopted for the study. The population of the study consisted of 834 technical drawing students from the six Edo State technical colleges. Purposive sampling technique, was used to obtain a sample size of 322 from the total population, two research instruments were used which include standardized Technical Drawing Achievement Test (TDAT), and Academic Self-Efficacy Scale (ASES). Standardized TDAT was adopted from the National Technical Certificate Examination past questions. The instrument on TDAT, was a standardize instruments and as such does not need any validation, however the instrument for (ASES) was validated by three research experts, two in Vocational and Technical Education Department of Ambrose Alli University, (AAU) Ekpoma and one from Measurement and Evaluation Department, University of Benin (UNIBEN), both from Edo state. Cronbach Alpha was used to determine the reliability coefficients of’ ASES questionnaire which yielded the reliability coefficient values of 0.84. One research question and one null hypothesis guided the study, the hypothesis was formulated and tested at .05 level of significance. 303 returned instruments were used for data analysis. Pearson Product Moment Correlation Co-efficient (PPMCC) was used for data analyses to answer the research question and linear regression was used to test the hypothesis at 0.05 level of significance. Results revealed a high positive correlation and relationship between self-efficacy and students’ academic performance in technical drawing in Edo State technical colleges. Based on this finding, it was recommended a system for early identification of disengaged students, providing targeted academic support and personalized mentorship pairings with experience teacher be implemented.